Western deconstructive intellectual projects and their impact on contemporary Arab political reality (قضايا سياسية, 2025)
The research focuses on the types of Western deconstructive intellectual projects that were first proposed in a way that linked their intellectual significance to the destruction and sabotage of everything that is central and established and working to fragment it and rebuild it anew, in a situation that expressed a revolution against rationality and science and the spread of doubt and the absence of truth and the destruction of moral values ​​by exporting deconstructive projects to the Arab world with various intellectual names and arguments, including spreading the principles of democracy, human rights, the right to differ and the anew reconstruction of human values.